2017
DOI: 10.1039/c7ra01617d
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical exploration on the electronic and magnetic properties of (FeCp)n– (n = 1, 2) ligand-functionalized graphene

Abstract: The spin density plots of (FeCp)2@Gi(i= 1–5).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…The interactions of organic molecules with metal atoms are garnering more and more interest in many areas of modern technology due to their geometries and electronic properties. Several experimental [1][2][3][4][5] and theoretical [6][7][8][9] works have been devoted to studying the structure and property of organometallic complexes. Transition metal atoms supported on benzene attract the special attention of scientists for many years, one of the more interesting findings of Kaya and coworkers showed that for the 3d transition metal, the early elements (Sc -V) interact with benzene to form multiple-decker sandwich structures, while the later elements (Fe -Ni) form rice-ball structures [10].…”
Section: Introductionmentioning
confidence: 99%
“…The interactions of organic molecules with metal atoms are garnering more and more interest in many areas of modern technology due to their geometries and electronic properties. Several experimental [1][2][3][4][5] and theoretical [6][7][8][9] works have been devoted to studying the structure and property of organometallic complexes. Transition metal atoms supported on benzene attract the special attention of scientists for many years, one of the more interesting findings of Kaya and coworkers showed that for the 3d transition metal, the early elements (Sc -V) interact with benzene to form multiple-decker sandwich structures, while the later elements (Fe -Ni) form rice-ball structures [10].…”
Section: Introductionmentioning
confidence: 99%